Importance of Early Detection of Acute Angle Closure Glaucoma: A Case Report - Lazuardiah Anandi; Sarah Yasmin Ramadhanti; Muhammad Yoserizal (Majalah Oftalmologi Indonesia, 2022)
Background: Acute Angle Closure Glaucoma is an ocular emergency that caused by a rapid increase in intraocular pressure due to outflow obstruction of aqueous humor. This condition can result visual losses that is irreversible so that early detection with the right diagnosis by general practitioner or ophthalmologist is vital to minimize the risk of permanent damage. We report the case of a patient who gained significant improvement after glaucoma surgery immediately after diagnosed with acute angle closure glaucoma in the ER. Case Presentation; A 53-year old female was presented with a chief complaint of throbbing pain and redness on both eyes (left eye (LE) at first, followed by right eye (RE)) for 3 days. She also had blurred vision, headache, and was unable to sleep due to the pain. Her presenting visual acuity (VA) was 20/80 in the RE and hand movements in the LE, with measured intraocular pressure (IOP) was 65 mmHg in the RE and 63 mmHg in the LE. After diagnosed with acute angle closure glaucoma and senile nuclear cataract on both eyes, a series of peripheral iridotomy laser followed with trabeculectomy was performed. Four weeks after the surgery, her VA is improved to 6/6 with corrected refraction and IOP is successfully lowered to 10mmHg on both eyes. Slit-lamp examination also showed an improvement of anterior chamber depth now that it is deep. Conclusion: Although degeneration of optic nerve due to glaucoma is deemed irreversible, our patient showed a significant improvement in visual function following surgery. Early detection and early intervention with surgery might play an important role in acute closure angle glaucoma to prevent further optic nerves damage and deterioration of visual function.